Interethnic Proximity and Political Development - Chun Chee Kok; Gedeon Lim; Danial Shariat; Abu Siddique; Shunsuke Tsuda (Institute of Labor Economics (IZA), 2025)
We exploit a population resettlement program of ethnic minorities in Malaysia to identify long-run effects of interethnic proximity on economic and political development. From 1948 to 1951, the colonial government moved 500,000 rural Chinese into hundreds of isolated, mono-ethnic camps. In ethnic majority Malay communities adjacent to these camps, we find greater economic prosperity and lower vote shares for the ethno-nationalist Malay party. Effects are stronger in areas with historical, interethnic economic complementarities. Primary survey data suggests that trust-building and social integration were key channels. Our findings highlight the importance of persistent, localized contact in the co-evolution of economic and political development.
Keywords: D72; O15; R23; J15; 330; Malaysia; development; political preference; ethnicity; Chinese